Interaction of Bacterial and Lambda Phage Recombination Systems in the X-Ray Sensitivity of Escherichia coli K-12 - Trgovčević, Željko (1974)
E. coli cells lysogenic for the thermoinducible prophage λcI857 can be transiently induced by a brief heat treatment. Although this treatment does not kill the cells, some λ products normally formed during vegetative phage development are made that can alter the response of host cells to x-irradiation by causing an increase in radioresistance. This increased resistance is particularly striking in the recombination-deficient recB-strain, which is normally much more radiosensitive than its recB(+) parent. After pulse-heating at 42°, the survival curve of E. coli recB(-) lysogenized with λcI857 does not differ from that of the wild-type strain. Since λ red mutants do not increase the radioresistance of recB(-) strains, both λ red gene products, λ exonuclease and β-protein, are required to compensate for the missing recB product. Furthermore, phage-induced radioresistance also occurs in recB(+) lysogens even when they carry λ red(-), but not when the λ prophage is gam(-). Thus, in wild-type cells, phage-induced radioresistance requires some interaction between the bacterial recB gene product (exonuclease V) and the phage λ-protein.